TRACHYONYCHIA ASSOCIATED WITH ALOPECIA AREATA AND SECONDARY ONYCHOMYCOSIS - Anggowarsito, Jose L.; Kandou, Renate T. (UNIVERSITAS SAM RATULANGI, 2014)
Abstract: Trachyonychia is an idiopathic nail inflammatory disorder that causes nail matrix keratinization abnormality, often found in children, and associated with alopecia areata, psoriasis, atopic dermatitis, or nail lichen planus. Trachyonychia could be a manifestation of associated pleomorphic or idiopathic disorders; therefore, it may occur without skin or other systemic disorders. There is no specific diagnostic criteria for tracyonychia. A biopsy is needed to determine the definite pathologic diagnosis for nail matrix disorder; albeit, in a trachyonychia case it is not entirely necessary. Trachyonychia assessment is often unsatisfactory and its management is focused primarily on the underlying disease. We reported an 8-year-old girl with twenty dystrophic nails associated with alopecia areata. Cultures of nail base scrapings were performed two times and the final impression was trichophyton rubrum. Conclusion: Based on the clinical examination and all the tests performed the diagnosis of this case was trachyonychia with twenty dystrophic nails associated with alopecia areata and secondary onychomycosis.The majority of trachyonychia cases undergo spontaneous improvement; therefore, a specific therapy seems unnecessary. Onychomycosis is often difficult to be treated. Eradication of the fungi is not always followed by nail restructure, especially if there has been dystrophy before the infection.Keywords: trachyonychia, alopecia areata, onychomycosis.Â Â Abstrak: Trakionikia adalah inflamasi kuku idiopatik yang menyebabkan gangguan keratinisasi matriks kuku, sering terjadi pada anak, dan terkait dengan alopesia areata, psoriasis, dermatitis atopik atau lichen planus kuku. Trakionikia bisa merupakan manifestasi dan asosiasi dari gangguan pleomorfik atau idiopatik, sehingga dapat terjadi tanpa kelainan kulit dan gangguan sistemik lainnya. Tidak terdapat kriteria diagnosis khusus untuk trakionikia. Diagnosis patologik definitif untuk kelainan matriks kuku ialah melalui biopsi, namun hal ini tidak disarankan. Penanganan trakionikia sering tidak memuaskan dan fokus manajemen terutama ditujukan pada penyakit yang mendasarinya. Kami melaporkan seorang anak perempuan berusia 8 tahun dengan dua puluh kuku distrofik disertai alopesia areata. Kultur dari kerokan dasar kuku dilakukan dua kali dengan hasil trichophyton rubrum. Simpulan: Berdasarkan pemeriksaan klinis dan pemeriksaan penunjang, diagnosis kasus ini ialah trakionikia dengan 20 kuku distrofik disertai alopesia areata dan onikomikosis sekunder. Mayoritas kasus trakionikia dilaporkan mengalami perbaikan spontan sehingga terapi khusus untuk trakionikia sering tidak diperlukan. Onikomikosis sering sulit diobati. Eradikasi jamur tidak selalu disertai perbaikan struktur kuku, terutama bila telah terjadi distrofi kuku sebelum infeksi.Kata kunci: trakionikia, alopesia areata, onikomikosis.